Secret shelf - Abdul Latif, Nur Athirah; Fazilli, Nurul Fadzlina; M Said, Salasiah (Universiti Teknologi MARA, Kedah, 2017)
Information agency serves different types of users. Each of users has their own preference while searching for the information. There is a need for libraries, to cater the user’s need to make sure they are feeling comfortable while in a library. Secret Shelf is one of new invention in an information agency. The problem arise in a library commonly regarding to the save space for the shelves, chair and many more. Other than that, user easy to feel bored with the same decoration in a library. In future, this shelf capable to fulfill the library needs. The novelty and uniqueness of this Secret Shelf is library is free to decorate the space in order to locate more books in a library. Users also can get advantage from this shelf because the collection is located nearby with the seats. In order to preserve the book lifetime, it is important to protect books from cold temperature.